Comparative evaluation of forestry carbon baseline between North Korea and Mongolia from Google Earth. (11th June 2021) - Um, Dan‐Bi
Abstract: This comparative empirical study on North Korea and Mongolia was conducted to demonstrate how satellite imagery extracted from Google Earth can be used to estimate the Reducing Emissions from Deforestation and forest Degradation (REDD) baseline. Forests in North Korea are eight times more densely distributed (8 471 787 hectares, 69.6% of its total land area) than that of Mongolia (12 842 624 hectares, only 8% of its total land area). Forests in North Korea have up to 10 times more carbon storage capacity (e.g. above‐ground biomass of Pinus koraiensis under the category of the temperate continental forest, IPCC Guideline: 58.23 ton) than that of Mongolia (e.g. above‐ground biomass of coniferous in boreal tundra woodland: 5 ton). Results are expected to be used as objective basic data in the process of introducing REDD+ to North Korea by verifying sharp differences between North Korea and Mongolia. The study could help companies preparing for carbon offset ventures in North Korea since it provides evidence for a more cost‐effective carbon credit than in Mongolia despite less initial investment and maintenance cost for forest plantation.